Ontogeny and Phylogeny of a New Hypotrichous Ciliate (Protista, Ciliophora), Metaurostylopsis alrasheidi n. sp., With Establishment of a New Genus Monourostylopsis n. gen. - Song, Wenya; Qiao, Yu; Dong, Jingyi; Bourland, William A.; Zhang, Tengteng; Luo, Xiaotian (Frontiers in Marine Science, 2020)
In the present study, based on both morphologic and phylogenetic analyses, a new genus, Monourostylopsis n. gen., and new species, Metaurostylopsis alrasheidi n. sp. as well as a new combination, Monourostylopsis antarctica (Jung et al., 2011) n. comb. (original combination: Metaurostylopsis antarctica Jung et al., 2011), are suggested. The new genus is diagnosed mainly by having three or more frontoterminal cirri, a midventral complex with midventral pairs and a single midventral row, one right marginal row and two or more left marginal rows. Based on live observation and protargol staining, the morphology and morphogenesis of a new species, M. alrasheidi n. sp. isolated from China, were investigated. The new species can be characterized by: two types of cortical granules; about 22 adoral membranelles; three or four frontoterminal, four or five transverse cirri; about eight midventral pairs and three or four unpaired midventral cirri; three or four left and right marginal rows. The main morphogenetic features of Metaurostylopsis alrasheidi n. sp. can be summarized as: 1) the entire parental ciliature, including the oral apparatus, is renewed; 2) the oral primordium of the proter originates probably within a pouch; 3) the oral primordium of the opisthe forms de novo on cell surface; 4) the anlagen of marginal rows and dorsal kineties are formed intrakinetally, and 5) the fusion of macronuclear nodules results in an irregular mass with few branches. In the phylogenetic trees, all the available Metaurostylopsis sequences cluster together in a clade with full support (ML/BI: 100/1.00) revealing that the genus is monophyletic within the large group of core urostylids.